Equilibrium in asset markets - Gregoire C., Jorge; Zurita, Salvador (Estudios de Administración, 1994)
This paper critically reviews the different models of equilibrium in asset markets. The survey includes the Sharpe-Lintner-Black model, and Roll´s critique, Merton´s intertemporal multibeta version in continuos time, the aggregate consumption model developed by Breeden, Ross´arbitrage pricing theory, and Grinblatt and Titman´s equilibrium arbitrage pricing theory in finite economies. Although the emphasis is on the theoretical work, the main empirical results are also outlined.